Minimal effects from injunctive norm and contentiousness treatments on COVID-19 vaccine intentions: evidence from 3 countries. Issue 2 (13th May 2022) - Carey, John M; Keirns, Tracy; Loewen, Peter John; Merkley, Eric; Nyhan, Brendan; Phillips, Joseph B; Rees, Judy R; Reifler, Jason
Abstract: Does information about how other people feel about COVID-19 vaccination affect immunization intentions? We conducted preregistered survey experiments in Great Britain (5, 456 respondents across 3 survey waves from September 2020 to February 2021), Canada (1, 315 respondents in February 2021), and the state of New Hampshire in the United States (1, 315 respondents in January 2021). The experiments examine the effects of providing accurate public opinion information to people about either public support for COVID-19 vaccination (an injunctive norm) or public beliefs that the issue is contentious. Across all 3 countries, exposure to this information had minimal effects on vaccination intentions even among people who previously held inaccurate beliefs about support for COVID-19 vaccination or its perceived contentiousness. These results suggest that providing information on public opinion about COVID vaccination has limited additional effect on people's behavioral intentions when public discussion of vaccine uptake and intentions is highly salient.